2015
DOI: 10.18632/oncotarget.6476
|View full text |Cite
|
Sign up to set email alerts
|

RAS-MAPK pathway epigenetic activation in cancer: miRNAs in action

Abstract: The highly conserved RAS-mitogen activated protein kinase (MAPK) signaling pathway is involved in a wide range of cellular processes including differentiation, proliferation, and survival. Somatic mutations in genes encoding RAS-MAPK components frequently occur in many tumors, making the RAS-MAPK a critical pathway in human cancer. Since the pioneering study reporting that let-7 miRNA acted as tumor suppressor by repressing the RAS oncogene, growing evidence has suggested the importance of miRNAs targeting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 128 publications
2
84
1
1
Order By: Relevance
“…Later, numerous other miRNA were discovered to target RAS or its effector molecules in numerous cancers 28 . There are several miRNA reported to target KRAS other than MIRLET7 29 . MIR96, MIR126 and MIR206 were downregulated in pancreatic cancer and functioned as tumor suppressors 30‐32 .…”
Section: The Association Of Ras Signaling Network With Cancer and MImentioning
confidence: 99%
“…Later, numerous other miRNA were discovered to target RAS or its effector molecules in numerous cancers 28 . There are several miRNA reported to target KRAS other than MIRLET7 29 . MIR96, MIR126 and MIR206 were downregulated in pancreatic cancer and functioned as tumor suppressors 30‐32 .…”
Section: The Association Of Ras Signaling Network With Cancer and MImentioning
confidence: 99%
“…Therefore, we speculated that PRKAR1A induces EMT by regulating Snail1. In our vitro experiments, we further elucidated that PRKAR1A deficiency up-regulated snail expression by the activation of ERK pathway, which was critical for the initiation and progression of numerous cancers414243. ERK kinase could activate Snail to further regulate EMT4445.…”
Section: Discussionmentioning
confidence: 73%
“…It is concluded that levels of plateletrelated plasma miRNAs and YRNAs correlate with platelet function tests in ACS patients and platelet stimulation markers in the general population and that changes in miR-126 affect platelet reactivity (Kaudewitz et al, 2016). An experimental-validated map of RAS-MAPK oncomiRs and tumour suppressor miRNAs from transmembrane receptor to downstream ERK proteins has been recently provided (Masliah-Planchon et al, 2016).According to which, MiRNAs could be further regarded as probable genetic biomarkers for diagnosis, prognosis, or therapeutic purpose. Mounting proof had suggested the importance of miRNAs targeting the RAS-MAPK in oncogenesis.…”
Section: Journal Of Molecular Biology Researchmentioning
confidence: 99%